2009
DOI: 10.1017/s1751731109003954
|View full text |Cite
|
Sign up to set email alerts
|

Can audio–visual or visual stimuli from a prospective mate stimulate a reproductive neuroendocrine response in sheep?

Abstract: Stimuli from a prospective mate increase the secretion of luteinising hormone (LH) in sheep. This 'male effect' in ewes and 'female effect' effect in rams is predominantly mediated by olfactory signals, though it is thought that non-olfactory signals play synergistic or substitutive roles. In this study, we tested whether exposure to visual or audio-visual stimuli from a prospective mate would stimulate an increase in LH secretion in ewes (Experiment 1) and rams (Experiment 2). In Experiment 1, groups of eight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…Nonolfactory stimuli also seem to be involved. A recent study reported that anestrous ewes respond to projected images of rams with an increase in LH secretion although the response is less intense compared with that observed in ewes exposed to real rams [32]. In goats, vocalizations also appear to stimulate LH secretion [33].…”
Section: Discussionmentioning
confidence: 96%
“…Nonolfactory stimuli also seem to be involved. A recent study reported that anestrous ewes respond to projected images of rams with an increase in LH secretion although the response is less intense compared with that observed in ewes exposed to real rams [32]. In goats, vocalizations also appear to stimulate LH secretion [33].…”
Section: Discussionmentioning
confidence: 96%
“…In a recent study by our group, ewes were seen to respond to photographs of rams with a small increase in LH secretion -the response was muted compared to ewes exposed to the full complement of sociosexual stimuli but it can be inferred that visual stimuli do play a role in mediating the neuroendocrine response of female ungulates to the male effect. Few studies have evaluated the role of auditory stimuli in the male effect but, in the same study, auditory signals from a movie of ewes and rams mating had no effect on pulsatile secretion of LH (50). Nevertheless, auditory stimuli might still be involved in individual recognition: first, auditory signals assist the recognition of lambs by their mothers, particularly from a distance (60); second, some breeds are more reliant on vocal cues than others (57) and, in turn, this could affect the mode or method of individual recognition between males and females.…”
Section: Is Identity Encoded By Olfactory Stimuli From the Male?mentioning
confidence: 99%
“…To address this issue, it is logical to begin with olfactory stimuli because there is general agreement that male odour has an important impact on female reproductive physiology and behaviour (44) and, alone, can induce the entire male effect, from the initial neuroendocrine response through to ovulation (44)(45)(46)(47)(48)(49)(50). Olfactory stimuli are known to mediate individual recognition between males and females of other species (51,52) so a logical hypothesis is that male identity is encoded primarily by an olfactory chemical 'fingerprint' or 'olfactory signature' .…”
Section: Is Identity Encoded By Olfactory Stimuli From the Male?mentioning
confidence: 99%
“…In sheep, the male pheromone seems to be a mix of long-chain fatty acids [34] that might be sufficiently complex to encode the identity of individual males [5]. However, visual stimuli are also important for social communication in sheep [35][36][37][38], and we recently found that projected images of male sheep elicit a small but significant neuroendocrine response in female sheep [39]. Therefore, further studies are required to elucidate the mechanism by which female sheep can discriminate between novel and familiar males.…”
Section: Pheromones and Cell Proliferation In A Female Ungulate 1149mentioning
confidence: 99%